2019
DOI: 10.3389/fphys.2018.01955
|View full text |Cite
|
Sign up to set email alerts
|

Gait Stability and Its Influencing Factors in Older Adults

Abstract: A stable gait pattern is a prerequisite to successfully master various activities of daily living. Furthermore, reduced gait stability is associated with a higher risk of falling. To provide specific intervention strategies to improve gait stability, gaining detailed knowledge of the underlying mechanism and influencing factors is of utmost importance. The effects of relevant influencing factors on gait stability are poorly examined, yet. Therefore, the aim of the current study was to quantify the effects of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 57 publications
0
62
0
1
Order By: Relevance
“…Gait parameters and LLE have been shown to depict reasonable construct and convergent validity (Bruijn et al 2013 ). In this study, we report stride time variability (sd) and LDS, as these parameters have been shown to be related to physical activity and balance performance in healthy and fall-prone older adults (Hamacher et al 2018 ; Hausdorff 2007 ), and have been used to characterize changes in gait due to diminished visual feedback (Hamacher et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Gait parameters and LLE have been shown to depict reasonable construct and convergent validity (Bruijn et al 2013 ). In this study, we report stride time variability (sd) and LDS, as these parameters have been shown to be related to physical activity and balance performance in healthy and fall-prone older adults (Hamacher et al 2018 ; Hausdorff 2007 ), and have been used to characterize changes in gait due to diminished visual feedback (Hamacher et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…As a basis to analyze the LDE, we reconstructed a state-space based on the threedimensional gyroscope (angular velocity) data which resulted in the highest effects in comparing the LDE of older vs. younger adults [13] and was, therefore, used in several studies (e.g., [26,27]). Since we used the calibrated gyroscope data outputted from the proprietary sensor fusion algorithm, we did not additionally implement any protocol to correct for time-dependent sensor errors.…”
Section: Data Processingmentioning
confidence: 99%
“…ower limb muscle strength, balance, and functional mobility are commonly occurring modifiable falls risk factors that are interrelated. 18 Deficits in 1 or more of these falls risk factors can have serious implications for older adults, such as increased risk for falls and fall-related injuries, greater dependency on others, diminished quality of life, and an increased likelihood of hospital stays. 6,12,50,55 For these reasons, multiple risk factors should be collected to better capture falls risk.…”
mentioning
confidence: 99%